The Impact of Onset to Hospital Admission Time on Clinical Outcome in Patients with Ischemic Stroke without Reperfusion Therapy (Central Asian Journal of Medical Sciences, 2018)
Objective: The narrow therapeutic window after stroke onset is a major concern in stroke treatment, especially in developing countries. This study aimed to investigate the correlation between onset to hospital admission time and clinical outcome in patients with ischemic stroke who did not receive reperfusion therapy. Method: A total of 313 patients with ischemic stroke were recruited in this retrospective cohort study. Data were obtained from the electronic stroke registry of Bethesda Hospital Yogyakarta, Indonesia. Ischemic stroke was diagnosed by well-trained neurologists and confirmed by brain CT-scan. Clinical outcome was assessed using the modified Rankin scale. Predictors of clinical outcome were assessed. Data analysis was conducted using multiple logistic regression. Results: The incidence of disability and death were 30.4% (95/313) and 7.6% (24/313) respectively. Multiple logistic regression analysis showed onset to hospital admission time greater than 6 hours (OR: 4.56; 95% CI:2.372- 8.792; p